Paradoxical Association Between Baseline Apolipoprotein B and Prognosis in Coronary Artery Disease: A 36,460 Chinese Cohort Study - Li, Huanqiang; Wang, Bo; Mai, Ziling; Yu, Sijia; Zhou, Ziyou; Lu, Hongyu; Lai, Wenguang; Li, Qiang; Yang, Yongquan; Deng, Jingru; Tan, Ning; Chen, Jiyan; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Apolipoprotein B (ApoB) and low-density lipoprotein cholesterol (LDL-C) were identified targets for blood lipid management among coronary artery disease (CAD) patients. However, previous studies reported an inverse correlation between baseline LDL-C concentration and clinical outcomes. This study aims to explore the definite association between baseline ApoB and long-term prognosis. Methods A total of 36,460 CAD patients admitted to Guangdong Provincial People's Hospital were enrolled and categorized into two groups: high ApoB (≥65 mg/dL) group and low ApoB (<65 mg/dL) group. The association between baseline ApoB and long-term all-cause mortality was evaluated by the Kaplan-Meier method, Cox regression analyses and restricted cubic splines. Results The overall mortality was 12.49% (n = 4,554) over a median follow-up period of 5.01 years. Patients with low baseline ApoB levels were paradoxically more likely to get a worse prognosis. There was no obvious difference in risk of long-term all-cause mortality when only adjusted for age, gender, and comorbidity (aHR: 1.07, 95% CI: 0.99–1.16). When CONUT and total bilirubin were adjusted, the risk of long-term all-cause mortality would reduce in the low-ApoB (<65 mg/dL) group (aHR: 0.86, 95% CI: 0.78–0.96). In the fully covariable-adjusted model, patients in the ApoB <65 mg/d group had a 10.00% lower risk of long-term all-cause mortality comparing to patients with ApoB ≥65 mg/dL (aHR: 0.90; 95% CI:0.81–0.99). Conclusion This study found a paradoxical association between baseline ApoB and long-term all-cause mortality. Malnutrition and bilirubin mainly mediate the ApoB paradox. Increased ApoB concentration remained linearly associated with an increased risk of long-term all-cause mortality.